Low-temperature atomic layer deposition delivers more active and stable Pt-based catalysts. Issue 30 (20th July 2017) - Van Bui, Hao; Grillo, Fabio; Kulkarni, Sri Sharath; Bevaart, Ronald; Van Thang, Nguyen; van der Linden, Bart; Moulijn, Jacob A.; Makkee, Michiel; Kreutzer, Michiel T.; van Ommen, J. Ruud
Abstract : We tailored the size distribution of Pt nanoparticles on graphene nanoplatelets at a given metal loading by using low-temperature atomic layer deposition. Abstract : We tailored the size distribution of Pt nanoparticles (NPs) on graphene nanoplatelets at a given metal loading by using low-temperature atomic layer deposition carried out in a fluidized bed reactor operated at atmospheric pressure. The Pt NPs deposited at low temperature (100 °C) after 10 cycles were more active and stable towards the propene oxidation reaction than their high-temperature counterparts. Crucially, the gap in the catalytic performance was retained even after prolonged periods of time (>24 hours) at reaction temperatures as high as 450 °C. After exposure to such harsh conditions the Pt NPs deposited at 100 °C still retained a size distribution that is narrower than the one of the as-synthesized NPs obtained at 250 °C. The difference in performance correlated with the difference in the number of facet sites as estimated after the catalytic test. Our approach provides not only a viable route for the scalable synthesis of stable supported Pt NPs with tailored size distributions but also a tool for studying the structure–function relationship.